Organic Amendments for Growth, Yield and Quality of Green Coriander (Coriandrum sativum L.) - Mausum Kumar Nath (Biology and Life Sciences Forum)
Fresh and green leafy vegetables are an inevitable part of human nutrition. Leafy coriander is one of the most important condiments in the world and requires adequate fertilizer input for higher production. Expanding population constraints have compelled many countries to use pesticides and fertilizers in order to boost farm production and fulfil their ever-increasing food demands. To stimulate the rapid and sumptuous growth of leafy vegetables like coriander, farmers apply a lot of nitrogenous fertilizers, resulting in poor quality and shelf lives. The application of organic amendments can solve this issue by improving the quality of coriander, as well as prolonging its shelf life. Moreover, various research work has been carried out in India and abroad on coriander as a seed spice, but limited research has been conducted on coriander as a condiment. Hence, this investigation was taken up. The experiment was prepared with seven treatments in a randomized block design and was replicated three times in the organic block of the Experimental Farm at Assam Agricultural University, India. The data from the respective field experiment were subjected to appropriate statistical analysis, as per the procedure proposed by Panse and Sukhatme. The result of the present investigation revealed that T7 (enriched compost @ 5 t ha−1) could produce the maximum yield with the highest benefit–cost ratio of 3.18, along with the best performance in terms of the quality of produce. Therefore, T7 can be inferred as farmer-friendly for sustainable production due to its efficiency, higher net return in comparison to other treatments, and minimal impact on the environment (and thus its adoption can be taken into consideration under field conditions).